A Method for Decision-Making on the Tendering procedure for the Acquisition of Goods and Services in Public Procurement - Jorge Manuel Macías Bermudez; Gisell Karina Arreaga Farias; Leonso Torres Torres (Neutrosophic Sets and Systems, 2020)
The legislation on public procurement in Ecuador has undergone a profound change with the issuance of the Organic Law of the National Public Procurement System and the use of tools generated by Information and Communication Technologies (ICT). The tender constitutes a contractual award procedure, provided for in this legal body. However, the selection of suppliers for certain non-standardized goods and services represents a conflict that is assumed by decision-makers in the tendering processes. This research proposes a solution to the problem posed from the development of a decision-making method on tenders for non-standard goods and services as part of the public procurement process.